A pulsar escaping an ancient open cluster via tidal stripping - Lei Zhang; Xiaoting Fu; Di Li; Emma Carli; Long Wang; Jiaqi Zhao; Craig O. Heinke; Emanuele Dalessandro; Yang Chen; Angela Bragaglia; Duncan R. Lorimer; Ewan D. Barr; et al. (Science Bulletin, 2026)

Surfactants as a strategy to enhance substrate uptake and transport in anaerobic bioreactors for process intensification - Henrique S. Dornelles; Giin-Yu Amy Tan; Emma Beirns; Theo Y.C. Lam; Maria A.T. Adorno; Carolina A. Sabatini; Maria B.A. Varesche; Po-Heng Lee (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Machine learning–driven nanoparticle–enhanced paper chromogenic array sensor approach for detecting sub-lethally injured Salmonella in low moisture food - Zhen Jia; Emma Grace Holliday; Elizabeth Catherine Tang; Haley Brynn Russo; Thomas R. Rootes; Yaguang Luo; Hengyong Yu; Dayang Wang; Boce Zhang (Food Research International, 2026)

Sorghum2035: A decadal vision for sorghum functional genomics and molecular breeding - Feifei Yu; Yongfu Tao; Lijing Liu; Peng Xie; Emma Mace; David Jordan; Qi Xie (Molecular Plant, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

GOOS Essential Ocean Variables: the backbone of a sustained and evolving global ocean observing system - Belén Martín Míguez; Emma Heslop; Narissa Bax; Lisandro Benedetti-Cecchi; Gabrielle Canonico; Kim Currie; Karen Evans; Albert S. Fischer; Véronique Garçon; Maria Hood; Johannes Karstensen; Ana Lara-López; et al. (Frontiers in Marine Science, 2026)
The need for ocean information has never been greater. From climate change to food security and extreme events, we need to understand the role of the ocean and better predict change and impact. This is only possible with the sustained collection of a key set of ocean observations. The Global Ocean Observing System (GOOS) coordinates international efforts to collect these Essential Ocean Variables (EOVs), which span physics, biogeochemistry, biology and ecosystem realms. Guided by three expert panels, these EOVs are used to define the needs and design of a sustained, fit for purpose global ocean observing system, aimed at maximizing investments in observing infrastructure. As the GOOS EOVs are increasingly used, it has become important to discuss and refine the understanding of this framework, to ensure that the right balance is struck between their essential nature and the need to expand to new domains and integrate with key global policies. In this paper we provide a description of the EOV framework, discuss some of the challenges in implementing it, and identify a set of recommendations for GOOS and the ocean observing community to take forward. These recommendations include increasing the transparency of the EOV adoption process, and the need to periodically assess the EOVs in consultation with observing communities and with the entities managing other global essential variable frameworks in cross cutting realms such as climate and biodiversity. This will contribute to building a useful and responsive global ocean observing system that delivers the observations required to meet societal needs.

Global ocean indicators: Marking pathways at the science-policy nexus - Karina von Schuckmann; Alex Godoy-Faundez; Véronique Garçon; Frank E. Muller-Karger; Karen Evans; Ward Appeltans; Narissa Bax; Lisandro Benedetti Cecchi; Anthony Bernard; Kim Bernard; Jarret Byrnes; Gabrielle Canonico; et al. (Marine Policy, 2026)

In Response to “Toward Balanced Curricula: Advancing Nondiet and Weight-Neutral Education in Dietetics” - Nicholas Slagel; Daniel Hall; Yu Wang; Zoe Duran; Katelyn Crawley; Dawn Clifford; Cristen Harris; Jeffrey Hunger; Emma Laing (Journal of Nutrition Education and Behavior, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Normalization of fossil plant megafossil databases for diversity and palaeobiogeography analyses by filtering taxonomic duplication: Principles, methods, examples, and recommendations - Zhen Xu; Emma Bateson; Christopher J. Cleal; Reece Hutton; Jianxin Yu; Shi-Jun Wang; Andrew H. Knoll; Benjamin J.W. Mills; Jason Hilton (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Chlorpyrifos selectively alters fluvial dissolved organic carbon composition and ecosystem dynamics - Lauren E. O'Connor; Jennifer J. Guerard; Emma J. Rosi; Yu-Ping Chin (Science of The Total Environment, 2025)

Genome-Wide Association Study of Glucocerebrosidase Activity Modifiers - Emma N. Somerville; Lynne Krohn; Konstantin Senkevich; Eric Yu; Jamil Ahmad; Farnaz Asayesh; Jennifer A. Ruskey; Dan Spiegelman; Stanley Fahn; Cheryl Waters; S. Pablo Sardi; Roy N. Alcalay; et al. (Molecular Neurobiology, 2025)
One of the most common genetic risk factors for Parkinson’s disease (PD) is variants in GBA1 , which encodes the lysosomal enzyme glucocerebrosidase (GCase). GCase deficiency has been associated with an increased PD risk, but not all individuals with low GCase activity are carriers of GBA1 mutations, suggesting other factors may be acting as modifiers. We aimed to discover common variants associated with GCase activity, as well as replicate previously reported associations, by performing a genome-wide association study using two independent cohorts: a Columbia University cohort consisting of 697 PD cases and 347 controls and the Parkinson’s Progression Markers Initiative (PPMI) cohort consisting of 357 PD cases and 163 controls. As expected, GBA1 variants have the strongest association with decreased activity, led by N370S (beta = − 4.36, se = 0.32, p = 5.05e − 43). We also identify a novel association in the GAA locus (encoding for acid alpha-glucosidase, beta = − 0.96, se = 0.17, p = 5.23e − 09) that may be the result of an interaction between GCase and acid alpha-glucosidase based on various interaction analyses. Lastly, we show that several PD-risk loci are potentially associated with GCase activity. Further research will be needed to replicate and validate our findings and to uncover the functional connection between acid alpha-glucosidase and GCase.

Incorporating Nondiet and Weight-Neutral Principles in a University Dietetics Curriculum - Nicholas Slagel; Daniel B. Hall; Yu Wang; Dawn Clifford; Cristen Harris; Jeffrey Hunger; Zoe Duran; Katelyn Crawley; Emma Laing (Journal of Nutrition Education and Behavior, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Marine turtles as bio-indicators of plastic pollution in the eastern Mediterranean - Emily M. Duncan; Hasan Deniz Akbora; Patrizia Baldi; Damla Beton; Annette C. Broderick; Burak Ali Cicek; Charlotte Crowe-Harland; Sophie Davey; Tess DeSerisy; Wayne J. Fuller; Julia C. Haywood; Yu Jou Hsieh; et al. (Marine Pollution Bulletin, 2024)

Multi-endpoint in vitro toxicological assessment of snus and tobacco-free nicotine pouch extracts - Fan Yu; Emma Bishop; Fabio Miazzi; Rhian Evans; David Smart; Damien Breheny; David Thorne (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Incidence of Dysphagia and Comorbidities in Patients With Cervical Dystonia, Analyzed by Botulinum Neurotoxin Treatment Exposure - Marjan Sadeghi; Ahunna Ukah; Emma Xiaomeng Yue; Kim Becker Ifantides; Nuo-Yu Huang; Joan Lee; Richard L. Barbano (Toxicon, 2024)

Active subduction and strain partitioning in western Myanmar revealed by a dense survey GNSS network - Eric O. Lindsey; Yu Wang; Lin Thu Aung; Jeng-Hann Chong; Qiang Qiu; Rishav Mallick; Lujia Feng; Pyae Sone Aung; Tha Zin Htet Tin; Saw Myat Min; Kyle Bradley; Oo Than; et al. (Earth and Planetary Science Letters, 2023)

NAT10 regulates the repair of UVB-induced DNA damage and tumorigenicity - Zizhao Yang; Emma Wilkinson; Yan-Hong Cui; Haixia Li; Yu-Ying He (Toxicology and Applied Pharmacology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Aerosolized aqueous dust extracts collected near a drying lake trigger acute neutrophilic pulmonary inflammation reminiscent of microbial innate immune ligands - Trevor A. Biddle; Keziyah Yisrael; Ryan Drover; Qi Li; Mia R. Maltz; Talyssa M. Topacio; Jasmine Yu; Diana Del Castillo; Daniel Gonzales; Hannah L. Freund; Mark P. Swenson; Malia L. Shapiro; et al. (Science of The Total Environment, 2023)

Superior methylparaben removal by anaerobic fluidized bed ceramic membrane bioreactor with PVDF tubular fluidized biocarrier: Reactor performance and microbial community - Junseok Heo; Daeeun Kwon; Emma Beirns; Giin-Yu Amy Tan; Po-Heng Lee; Jeonghwan Kim (Journal of Environmental Chemical Engineering, 2023)

Effects of spatially heterogeneous lakeside development on nearshore biotic communities in a large, deep, oligotrophic lake - Michael F. Meyer; Ted Ozersky; Kara H. Woo; Kirill Shchapov; Aaron W. E. Galloway; Julie B. Schram; Emma J. Rosi; Daniel D. Snow; Maxim A. Timofeyev; Dmitry Yu. Karnaukhov; Matthew R. Brousil; Stephanie E. Hampton (Limnology and Oceanography, 2022)
Sewage released from lakeside development can reshape ecological communities. Nearshore periphyton can rapidly assimilate sewage‐associated nutrients, leading to increases of filamentous algal abundance, thus altering both food abundance and quality for grazers. In Lake Baikal, a large, ultra‐oligotrophic, remote lake in Siberia, filamentous algal abundance has increased near lakeside developments, and localized sewage input is the suspected cause. These shifts are of particular interest in Lake Baikal, where endemic littoral biodiversity is high, lakeside settlements are mostly small, tourism is relatively high (~1.2 million visitors annually), and settlements are separated by large tracts of undisturbed shoreline, enabling investigation of heterogeneity and gradients of disturbance. We surveyed sites along 40 km of Baikal's southwestern shore for sewage indicators—pharmaceuticals and personal care products (PPCPs) and microplastics—as well as periphyton and macroinvertebrate abundance and indicators of food web structure (stable isotopes and fatty acids). Summed PPCP concentrations were spatially related to lakeside development. As predicted, lakeside development was associated with more filamentous algae and lower abundance of sewage‐sensitive mollusks. Periphyton and macroinvertebrate stable isotopes and essential fatty acids suggested that food web structure otherwise remained similar across sites; yet, the invariance of amphipod fatty acid composition, relative to periphyton, suggested that grazers adjust behavior or metabolism to compensate for different periphyton assemblages. Our results demonstrate that even low levels of human disturbance can result in spatial heterogeneity of nearshore ecological responses, with potential for changing trophic interactions that propagate through the food web.

Complete genome of the thermophilic purple sulfur Bacterium Thermochromatium tepidum compared to Allochromatium vinosum and other Chromatiaceae - W. Matthew Sattley; Wesley D. Swingley; Brad M. Burchell; Emma D. Dewey; Mackenzie K. Hayward; Tara L. Renbarger; Kathryn N. Shaffer; Lynn M. Stokes; Sonja A. Gurbani; Catrina M. Kujawa; D. Adam Nuccio; Jacob Schladweiler; et al. (Photosynthesis Research, 2022)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

In vitro Inhibition of Clinical Isolates of Otitis Media Pathogens by the Probiotic Streptococcus salivarius BLIS K12 - Tzu Yu Chen; John D. F. Hale; John R. Tagg; Rohit Jain; Abigail L. Voss; Nikki Mills; Emma J. Best; Duncan S. Stevenson; Philip A. Bird; Tony Walls (Probiotics and Antimicrobial Proteins, 2021)